A Poly(Propylene Imine) Dendrimer and Carbon Black Modified Flexible Screen Printed Electrochemical Sensor for Lead and Cadmium Co‐detection. Issue 12 (28th October 2020) - Mazzaracchio, Vincenzo; Tshwenya, Luthando; Moscone, Danila; Arduini, Fabiana; Arotiba, Omotayo A.
Abstract: Towards the development of miniaturised and low‐cost sensors for heavy metals detection in water, herein we describe an electrochemical sensor for the co‐detection of lead and cadmium. The sensor was developed using screen‐printed electrode modified with a composite of poly(propylene imine) dendrimer and carbon black. The electrode was modified by drop casting of the carbon black and electrodeposition of the poly(propylene imine) dendrimer. This modified electrode (sensor) was characterised by cyclic voltammetry and electrochemical impedance spectroscopy, revealing improved electrochemical performances. Square wave anodic stripping voltammetry (SWASV) was used to achieve the simultaneous detection of Pb(II) and Cd(II) at trace level, obtaining satisfactory LOD of 3.6 ppb and 15.3 ppb respectively; and sensitivity of 0.49 μA/ppb and 0.57 μA/ppb in tap water. Abstract :